Halal Certification Obligations for MSMEs: Analysis of Legal Supervision and Compliance Strategy in Kopen Village, Teras District, Boyolali Regency - Ferdian Raid Naufal; Diana Setiawati (Universitas Muhammadiyah Surakarta, 2026)
This study examines the laws and regulations governing halal certification obligations, analyzes compliance strategies and challenges faced by MSMEs in fulfilling halal certification obligations, and analyzes internal and external factors that hinder the fulfillment of these obligations. This research is a qualitative descriptive study with an empirical legal approach. Data collection methods were conducted through interviews and documentation. Data analysis was conducted using Soerjono Soekanto's theory of legal effectiveness using the Miles & Huberman interactive model. This research was conducted in a village that has never been studied before, taking two perspectives simultaneously: the authorized institution and the MSME actors. This study aims to inTo empirically analyze the effectiveness of law enforcement regarding halal certification obligations for MSMEs in Kopen Village, Boyolali Regency. As a center of the shrimp rind industry, Kopen Village faces unique challenges between state administrative obligations and traditional economic practices. Using Soerjono Soekanto's theory of legal effectiveness and the Miles & Hubberman model, this study reveals that the main obstacle lies not in regulations, but rather in the community's legal culture, which prioritizes social trust and limited digital resources. Field findings indicate that the uncertainty of the raw material supply chain from collectors is a critical point hindering certification. The government responded to this reality by postponing the obligation until October 2026 to provide space for more inclusive technical preparation and education. The results of the study indicate that there are laws and regulations governing the halal certification obligation, as well as compliance strategies and challenges faced by MSMEs in the process of fulfilling compliance, both internal and external factors. The results also indicate that these factors are influenced by the relationship between law, law enforcement, facilities or means, and society.